Chitosan from milkfish (Chanos chanos) scales and tiger shrimp (Panaeus monodon) shells wastes as corrosion inhibitor on ASTM A36 steel - Silvia, Chandra; Munir, Misbakhul; Maisaroh, Dian Sari (UIN Sunan Ampel Surabaya, 2021)
Chitosan synthesized from milkfish (Chanos chanos) scales and tiger shrimp (Panaeus monodon) shells were used as corrosion inhibitors on ASTM A36 steel. Milkfish scales and tiger shrimp shells wastes is extracted into chitosan through deproteination, demineralization and deacetylation process. The yield of milkfish scales and tiger shrimp chitosan was 31,81% and 67,16%, respectively. Corrosion rate testing using weight loss method then calculates inhibition efficiency of each inhibitor. The immersion test of specimens was carried out for four weeks with weight measurements every week. The concentrations used were 0 ppm as negative control; 60 ppm, 500 ppm and 1000 ppm for chitosan inhibitor; and 1000 ppm sodium nitrite as positive control. Inhibition efficiency values ​​produced by milkfish scales chitosan, starting from the first to the fourth week immersion, for concentration of 60 ppm were 43.9%, 46.8%, 48.9%, and 40.8%; for concentration of 500 ppm were 43.6%, 43.3%, 37.8%, and 17.8%; and for concentration of 1000 ppm were 37.5%, 44.9%, 39%, and 21.8%; while for tiger shrimp shells chitosan for concentration of 60 ppm were 37.6%, 51%, 34.6%, and 28.5%; for concentration of 500 ppm were 57.7%, 38.2%, 37.7%, and 19.6%; and for concentration of 1000 ppm were 48.6%, 41.2%, 37%, and 21.3%. Comparison of inhibition efficiency between chitosan from milkfish scales and tiger shrimp shells based on the statistical analysis One Way ANOVA resulted in a sig >0.05 which indicates a similarity in the efficiency value of chitosan from milkfish scales and tiger shrimp shells.